+0  
 
+1
61
1
avatar

The expression 3(log(x + 1) + log(x + 4)) can be written as log(z). What is z?

 

Here's my work:

3(log(x + 1) + log(x+4))

= 3log(x + 1) + 3log(x + 4)

= log(x + 1)^3 + log(x + 4)^3

= log[((x + 1)^3)((x + 4)^3)]

 

Therefore z = ((x + 1)^3)((x + 4)^3)

 

Is this correct?

 Aug 12, 2020
 #1
avatar+110682 
+1

Hi,

thanks for showing your effort.

Here is my answer.

 

\(3[log(x + 1) + log(x + 4)]\\ =3log[(x + 1)(x + 4)]\\ =log[(x + 1)(x + 4)]^3\\ \)

 

Yes, our answers are the same.  Good work :)

 Aug 13, 2020

12 Online Users

avatar
avatar